Educational Program on Sexuality for Adolescents with Congenital Heart Disease at the William Soler Pediatric Cardiocenter - Amalia Cánovas Rodríguez (Revista Finlay)
Background: congenital heart diseases are frequent malformations and constitute a health problem. People with congenital heart disease when they reach their adolescence show doubts about their sexuality. Ignorance about these issues promotes unhealthy practices and negative emotions that affect their well-being. Objective: to develop an educational program on sexuality for adolescents with congenital heart disease who are treated at the William Soler Pediatric Cardiocenter. Methods: a qualitative research was carried out using a dialectical paradigm at the William Soler Pediatric Cardiocenter during the period from 2019 to 2021. The used instruments in the research were: observation, interview, focus group, documents analysis and recording of anecdotes. Special educational needs on sexuality were described as the main category, as well as those difficulties in cognitive, emotional and psychosocial aspects that people may have in their learning process about sexuality on a temporary or lasting basis. Descriptive statistics and data analysis were used to delve into this phenomenon. Results: special educational needs on sexuality were identified in the adolescents studied, such as: lack of information, stereotypes and limited knowledge, difficulties in personal and couple relationships, affectations in self-assessment processes, lack of knowledge about gender, sexual health, congenital heart disease, changes in adolescence, contraception and family planning. Conclusions: the proposed program constitutes a tool for the knowledge modification, attitudes and behaviors towards sexuality. In addition, it is intended to contribute to the development of other skills such as socialization, decision-making and autonomy.